2018
DOI: 10.3390/atmos9060219
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Thermodynamic Factors Associated with Different Precipitation Regimes over South China during Pre-Monsoon Season

Abstract: Nine precipitation regimes over South China are obtained by applying the Self-Organizing Map (SOM) technique to the sub-daily precipitation during the pre-monsoon season (April to June) of 1979-2015. These nine regimes are distinct from each other in terms of precipitation amount and spatial pattern. The relationships between precipitation and different atmospheric dynamic and thermodynamic factors (large-scale divergence, water vapor flux, low-level jet, precipitable water, convective available potential ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…e convective available potential energy (CAPE) in the WRF skew-T (Figures 14 and 15) showed enhanced instability in the atmosphere for convective processes. It has been established that low level convergence (i.e., at 925 hPa pressure level) of moisture and upper level divergence are good indicators for large scale precipitation [40,41]. However, localized moisture convergence and mesoscale lifting could also produce a water-saturated cloud layer from which deep moist convection subsequently evolves [42].…”
Section: Wind and Moisturementioning
confidence: 99%
“…e convective available potential energy (CAPE) in the WRF skew-T (Figures 14 and 15) showed enhanced instability in the atmosphere for convective processes. It has been established that low level convergence (i.e., at 925 hPa pressure level) of moisture and upper level divergence are good indicators for large scale precipitation [40,41]. However, localized moisture convergence and mesoscale lifting could also produce a water-saturated cloud layer from which deep moist convection subsequently evolves [42].…”
Section: Wind and Moisturementioning
confidence: 99%
“…If so, where are the moisture sources for these extreme precipitation days located? Previous studies have shown that the ocean can provide abundant moisture supplies for extreme precipitation days over different regions (Boutle et al, ; Dacre et al, ; Gimeno et al, ; Gustafsson et al, ; Ma et al, ; Matrosov, ; Moore et al, ; Smith et al, ; Stohl & James, ). However, unlike the coastal areas of China and Japan, most of northeastern China is located far from the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Around 88% true detection is achieved with a relatively high false alarm rate of approximately 44% with these threshold values. So, rainfall is most likely to occur when these two conditions get satisfied, but there are also some other dynamic factors like thermodynamic variation involving large-scale divergence, water vapor flux, low-level jet, precipitable water, convective available potential energy, K index, heat divergence and enhancement of water vapor content in the atmosphere as well as some imperative atmospheric parameters like PWV, and atmospheric residual which are equally important for the rainfall to get triggered [8,224,225]. In the next section, we will introduce another atmospheric parameter in combination with gradient and compare the accuracy of that model.…”
Section: Threshold Values For Gradient Magnitude and Gradient Slope P...mentioning
confidence: 99%